(untitled) (Journal of Dhaka National Medical College & Hospital, 2023)
Background: Chronic calculus cholecystitis is an inflammatory disease which affects the gallbladder wall, accompanied by presence of gallstones in the gallbladder lumen, and reveals as biliary pain. Early and accurate diagnosis allows prompt treatment and reduces morbidity and other complications. Objectives: To observe the diversity of the demographic and clinical presentation of diagnosed chronic calculus cholecystitis. Methods: This is a descriptive type of observational study which was conducted at Department of Surgery, Dhaka National Medical College Hospital, over a period of 12 months from 6th December 2017 to 5th December 2018. Total 150 patients of chronic calculus cholecystitis with laboratory profile, ultrasonography proven in Surgery Department of Dhaka National Medical College Hospitals were included. Comparison was done by tabulation and graphical presentation in the form of tables, pie chart, bar diagrams etc. Results: In this study, the maximum number of patients (33.33%) was between 31-40 year age group, mean age of the patient was 42.5 ± 12.94 years. Out of 150 cases (73%) cases were female and (27%) were male. Female-male ratio was 2.75:1. Large numbers of respondents came from urban area 93 (62%), followed by rural area 57 (38%). Total 54 patients were obese among them male 11(27.5%) and female 43 (39.09% ) . Overweight patient found 51 among them 13(32.5%) were male and 38(34.54%) were female. Nutritional status was normal in 32 patients. Maximum numbers of female patients 65 (59.09%) had history of taking oral contraceptive pill during their reproductive period.Large number of respondents were house wife (41.33%) followed by service holder (20%). Socioeconomically 77(51%) comprising the major percentage of the patients is in middle class, which is followed by poor class 46(31%) and remaining are upper class 27(18%). The highest percentage has complained of upper abdominal pain in 80%. Among them 40.66% (61/150) patients had dull aching type. Most of the patients had complaint of flatulent, dyspepsia 78.66% (118/150). Many patients also had complaints of fatty food intolerance 64.66% (97/150). Although 20% patient was asymptomatic. Conclusion: Chronic calculus cholecystitis is a common problem in surgical practice. Patient may present with variable demographic presentation and upper abdominal pain along with flatulent, dyspepsia is the most common symptom. For early diagnosis accurate history taking, clinical examinations and investigations are vital. J. Dhaka National Med. Coll. Hos. 2023; 29 (01): 07-11